2019
DOI: 10.1104/pp.19.00487
|View full text |Cite
|
Sign up to set email alerts
|

The FATTY ACID DESATURASE2 Family in Tomato Contributes to Primary Metabolism and Stress Responses

Abstract: The conversion of oleic acid (C18:1) to linoleic acid (C18:2) in the endoplasmic reticulum is critical to the accumulation of polyunsaturated fatty acids in seeds and other tissues, and this reaction is catalyzed by a D12-desaturase, FATTY ACID DESATURASE2 (FAD2). Here, we report that the tomato (Solanum lycopersicum) genome harbors two genes, SlFAD2-1 and SlFAD2-2, which encode proteins with in vitro D12-desaturase activity. In addition, tomato has seven divergent FAD2 members that lack D12-desaturase activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 100 publications
0
28
0
Order By: Relevance
“…The latter is in line with the decrease in the plastid membrane trienoic fatty acids (Figure 3). In the present study, a specific 16:0-MGDG Δ7-desaturase (FAD5) coding gene was found to be highly up-regulated after H. In addition, major differences were detected in ER lipid biosynthetic gene transcripts in the H B3 samples, where the highly expressed gene coding for 18:1-phosphatidylcholine ω6 desaturase (FAD2-1, Lee et al, 2020) isoform and 16:2/18:2 galactolipid ω3 desaturase (FAD3, Yu et al, 2009) were repressed.…”
Section: Lipid Metabolismmentioning
confidence: 54%
“…The latter is in line with the decrease in the plastid membrane trienoic fatty acids (Figure 3). In the present study, a specific 16:0-MGDG Δ7-desaturase (FAD5) coding gene was found to be highly up-regulated after H. In addition, major differences were detected in ER lipid biosynthetic gene transcripts in the H B3 samples, where the highly expressed gene coding for 18:1-phosphatidylcholine ω6 desaturase (FAD2-1, Lee et al, 2020) isoform and 16:2/18:2 galactolipid ω3 desaturase (FAD3, Yu et al, 2009) were repressed.…”
Section: Lipid Metabolismmentioning
confidence: 54%
“…FAD2 encodes 12-desaturase that catalyzes the conversion of oleic acid (C18:1) to linoleic acid (C18:2) (Ohlrogge and Browse, 1995). The Arabidopsis genome has only a single FAD2 gene (AT3G12120), but most other plant species carry multiple FAD2 homologs (Cao et al, 2013;Lee et al, 2020). The duplication of FAD2 genes in plants would have enabled the functional diversification of these enzymes, leading to divergent catalytic activities and the synthesis of novel metabolites.…”
Section: Infection With A2-o Induces Genes Related To Defense Responsesmentioning
confidence: 99%
“…The duplication of FAD2 genes in plants would have enabled the functional diversification of these enzymes, leading to divergent catalytic activities and the synthesis of novel metabolites. For example, recent studies have shown that tomato has non-canonical FAD2 family proteins that lack 12-desaturase activity (Jeon et al, 2020;Lee et al, 2020). In particular, ACET1a/b (Solyc12g100240 and Solyc12g100260) and FAD2-9 (Solyc12g100250) are noncanonical FAD2 involved in the biosynthesis pathway from linoleic acid to a phytoalexin, falcarindiol (Jeon et al, 2020).…”
Section: Infection With A2-o Induces Genes Related To Defense Responsesmentioning
confidence: 99%
“…However, the high linoleic acid content of tobacco seed oil is problematic from the perspective of oxidative stability, which is important for industrial applications [1,3]. Low linoleic acid and high oleic acid content are preferred in nearly all oil seed crops breeding, and high oleic acid cultivars have been generated by selecting for or engineering reduced FAD2 activity [55]. In this paper, four FAD2 genes were firstly identified from tobacco genome (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that FAD2 genes play crucial roles in response to various abiotic stresses, such as chilling temperature [60,[67][68][69] and salt [70]. Most recently, FAD2 genes were demonstrated to be responsible for biotic stress in tomato [55]. The house-keeping NtFAD2-1 genes sequence were highly similar with the seed-type NtFAD2-2 genes.…”
Section: Crispr-cas9 System Was a Useful Tool For Tobacco Breedingmentioning
confidence: 91%